Daniel Buren, the ample field of painting, the place where genders are dissolved. An intervention projet in Puente de Rande (Vigo) - Castro-Fernández, Xosé Antón; Herranz-Pascual, Yolanda; Pastor-Bravo, Jesús (Arte, Individuo y Sociedad, 2018)
Beginning with a project to intervene in Puente de Rande in Vigo (Project pour la Galice, 2005) that would never come to fruition, its authors, who accompanied the artist for several days, researched and studied his approach while taking into account his methodical conception. In this methodology are the keys to his work: from a consensual point of view and a projectual discussion to his reconsideration of the use of public spaces and/or museums, making use of his well-known visual resource —the bands of color— and the affirmation of a piece as a "transformation of a place of welcome", while also taking into account the architecture, design and drawing, light and color, the context as nature of the place, and a feeling of endurance that exalts the essential image of the ephemeral, transcribed, as usual, in its photo-souvenirs and in the possibility of expanded painting. Resumen A partir de un proyecto para intervenir el Puente de Rande, en Vigo (Project pour la Galice, 2005), que nunca llegaría a realizarse, los autores, que acompañaron durante varios días al artista, investigan y estudian sus planteamientos, teniendo en cuenta su concepción metodológica. En ella están las claves de su trabajo, desde el consenso y la discusión proyectual, a su reconsideración del in situ en los espacios públicos o en el museo, haciendo uso de su reconocido útil visual más identitario –las bandas de color– y la afirmación de una obra como “transformación de lugar de acogida”, teniendo en cuenta la arquitectura, el diseño y el dibujo, la luz y el color, el contexto como naturaleza del lugar y un sentimiento de perdurabilidad que exalta la imagen esencial de lo efímero, transcrita, de manera habitual, en sus photos-souvenirs y en la posibilidad de una pintura de campo amplio.